Experimental Investigation and Optimization of Non-Catalytic In-Situ Biodiesel Production from Rice Bran Using Response Surface Methodology Historical Data Design - Siti Zullaikah; Ari Krisna Putra; Fathi Haqqani Fachrudin; Rosada Y Naulina; Sri Utami; Rifky P Herminanto; Orchidea Rachmaniah; Yi Hsu Ju (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Rice bran oil (RBO)is claimed to be a potential feedstock for biodiesel production. Non-catalytic in-situ biodiesel production from a low-cost feedstock (rice bran) using subcritical ethanol-water mixture was investigated in this study. The influence of four independent variables, i.e., addition of co-solvent, ethanol concentration, temperature, and time of reactions, on the yield of biodiesel was examined. The results showed that the most effective co-solvent wasethyl acetate and the optimum ethanol concentration, temperature and reaction time were 80% v/v, 200 oC and 3 hours, respectively. The maximum yield of biodiesel was found to be around 80%. The optimization of operating conditions was carried out by response surface methodology (RSM) with historical data design (HDD). The statistical method also suggested similar optimum operating conditions, i.e., 78.44% (v/v) ethanol concentration, 200 oC, and 3.2 hours reaction time with ethyl acetate as a co-solvent. The predicted maximum biodiesel yield was also slightly lower, i.e., 76.98%. Therefore, this study suggests that biodiesel production from rice bran through a non-catalytic in-situ process using a subcritical ethanol-water mixture with ethyl acetate as a co-solvent is very feasible since the yield can reach 80%. The study also found that RSM with HDD can predict the optimum operating conditions with a good accuracy.